PENGARUH BUDAYA TERHADAP STRATEGI REKRUTMEN DAN SELEKSI DALAM ORGANISASI MULTINASIONAL: PENDEKATAN SYSTEMATIC LITERATURE REVIEW - Zulfikar Akbar; Malik Ibrohim (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyse the influence of local culture on recruitment and selection processes in multinational companies, as well as the challenges faced in integrating cultural values with global recruitment policies. Local culture plays an important role in shaping the mindset and behaviour of candidates and influencing their expectations of the organisation. Therefore, companies operating in diflerent countries need to adjust their recruitment and selection strategies to accommodate cultural diflerences. This research examines how culture influences the selection process, especially in the context of Indonesia as a country with high cultural diversity. Using a qualitative approach and literature review, this research found that understanding local culture can improve the eflectiveness of recruitment and selection. The main challenge faced is creating a balance between the company's global standards and sensitivity to local social and cultural norms. The results of this study provide insights into how companies can design more inclusive and eflective recruitment strategies, as well as how technologies such as e-recruitment can play a role in creating greater diversity in the work environment.